A Prospective Evaluation of Patient-Reported Opioid Utilization After Nonoperative Treatment of Fractures and Dislocations. (18th July 2018) - Zhu, Hongyi; Gao, Yanchun; Zhang, Changqing; Zheng, Xianyou
Abstract : Background: Prescription of opioid analgesics is currently a common practice to relieve pain for musculoskeletal injuries in many regions of the world, especially in the United States and Canada. However, overprescription may underlie opioid misuse. Details on the utilization of prescribed opioids after nonoperative treatment of fractures and dislocations and whether consumption is related to injury location are unknown. Methods: A total of 1, 513 consecutive patients in China who underwent nonoperative treatment of a fracture and/or dislocation and who were prescribed opioids were studied over a 3-month period. Demographic information, alcohol consumption, smoking status, injury location, volume of prescription, and consumption patterns were recorded and were summarized. Results: The mean number of opioid pills prescribed was 14.7, and the mean patient-reported number of pills consumed was 7.2. Overall, 152 patients (10.0%) reported taking no prescribed opioid analgesics, and 924 patients (61.1%) ceased their prescribed opioids prior to completing the regimen. Injury location, alcohol consumption, and type of fracture or dislocation were all significantly associated with the patient-reported number of opioid pills consumed (p < 0.05). Patients with fracture and/or dislocation of the wrist or forearm (9.4 pills for 3.8 days); ankle, tibia, or fibula (9.3 pills for 3.7 days); or elbow or humerus (9.1 pills for 3.7 days) used more opioid pills compared with patients with injuries at other locations (not exceeding 6.4 pills and 3 days). When compared with patients who had no, low, or moderate daily alcohol consumption, there was more opioid use in patients with high daily alcohol consumption (8.5 pills for 3.4 days) and those with very high daily alcohol consumption (11.3 pills for 4.7 days). Patients with a dislocation and/or displaced fracture reported consuming 8.2 pills for 3.3 days, which was more than the consumption in patients with a nondisplaced fracture (6.2 pills for 2.5 days) and patients with an avulsion fracture (6.2 pills for 2.5 days). Conclusions: Surgeons and patients should try to avoid opioids if possible after nonoperatively treated fractures and dislocations. If opioids are used, surgeons should prescribe the smallest dose for the shortest time after considering the injury location and type of fracture or dislocation. Level of Evidence: PrognosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.